(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The psycho-emotional stress is an integral part of the life of modern young people. The level of free salivary cortisol was studied in 23 young healthy people (university students) during the intersessional period and the examination period. The enzyme immunoassay method was used. The subjects were divided into two groups: group 1 – with high learning efficiency, group 2 – with low learning efficiency. The following results were obtained: a sharp increasing of cortisol level at the time of the influence of a strong psycho-emotional factor (for example, an exam for a student) has a mobilizing effect on the human nervous system and the body as a whole, which is confirmed by highly effective results of academic performance. On the contrary, high levels of salivary cortisol during a period of moderate psycho-emotional environmental background (for example, the intersessional period) are a marker of a student’s chronic stress, which sharply reduces the mobilizing effect of cortisol in the corresponding life stages of the student, which is reflected in low results in the effectiveness of educational activities.